The big hit - Zide, Warren; Snipes, Wesley; TriStar Pictures (Culver City, CA : Columbia TriStar Home Video, 1998)
The criminal anarchy is hilarious when a foursome of full-time hit men looking to score extra cash kidnap the boss' goddaughter. And when beleaguered wise guy Mel is set up to take the fall, underworld antics and domestic absurdities collide for a working weekend no one will soon forget
Title from title screen
Screenplay, Ben Ramsey ; music, Graeme Revell
Cast: Mark Wahlberg, Iou Diamond Philips, Christine Applegate, Bokeem Woodbine, Antonio Sabato jr.
VCD format
Keywords: Suspense in motion pictures; Murderers -- Drama; Kidnapping -- Drama